Ayurvedic Management of Shwitra (Vitiligo) through Shaman Chikitsa: A Case Report - Manisha Vaman Davkare; Ashvini Dinesh Pardhekar (Journal of Clinical and Diagnostic Research)
In Ayurveda, all skin disorders are considered under the category of Kushta roga. These skin conditions impact not only an individual’s quality of life but also their psychological state of mind, social welfare, and economic development. Shwitra is one of the prevalent manifestations of skin problems. According to modern medicine, it is correlated with Vitiligo, and as a distributed type, it is categorised under Vulgaris Vitiligo subtype. White discoloured patches on the body are hallmark of Shwitra (Vitiligo). Hereby, the authors present a case report of 43-year-old female who came to Kayachikitsa Outpatient Department (OPD) with the complaints of white discoloured patches over face, majorly periorbital area, associated with mild itching and no burning sensation since 9-10 months. Considering the patient’s symptoms and indicators, the treatment strategy was shown to be successful in reversing the depigmented patches to re-pigmentation; more improvements could be achieved in the future by extending the use of other drug combinations based on various Ayurvedic characteristics. It was revealed that the patient’s condition had significantly improved.